Public Relations Management at Family Institutions in Moral Education - Mu’min, Dian Arifatul; Diantoro, Fery (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Socio-cultural developments and changes indirectly affect children's development and education. This situation affects children, who are basically looking for someone who can become their philosophy of life, making it difficult for families to fulfill their obligations to educate their children. Society has a great influence on the ongoing activities related to education, and family education is the earliest educational institution in human civilization. Before knowing formal education, the position and role of the family in human life is very important, because it is the most basic. the most active and widespread in history. No age limit (covers multiple age groups), no time limit, anytime, anywhere. The purpose of this study was to describe the role of the family in education in public relations management. This study was conducted using a qualitative method, in which appropriate multi-reference studies were used, and then comparisons were made. The family, school and community environment is the center of education, but of the three, the family environment has the greatest influence on children's development. The result of this research is that this family education is basic education, because children get the first education in this family. In addition, family education has a great impact on children's lives, especially on children's psychological growth and development, as well as on social and religious values. Keyword : Family, Public, Education